Propuesta de aprovechamiento integral de los residuos orgánicos provenientes del conjunto residencial La Colina (2020)
The development of this project is a proposal for the use of organic solid waste generated in the La Colina Residential Complex located in the city of Sogamoso, in the department of Boyacá; The recovery of this organic matter is carried out for the production of organic fertilizer and at the same time reduces the volume of household waste that ends up in the landfill. In this way it contributes to the preservation of the environment, providing benefits as a fertilizer that provides nutrients to plants and shrubs, the recovery of recyclable materials and reducing the impact of the entry of waste into the landfill, mitigating greenhouse gas emissions that are caused by the increase in waste that comes to this place.